ANTI-INFLAMMATORY EFFECT OF LICORICE DRY EXTRACT ON THE MODEL OF ACUTE PERITONITIS IN RATS - Березняков А. В. (World of Medicine and Biology, 2014)
Antiexudative activity of licorice dry extract on the model of acute peritonitis in rats studied. The results indicate a pronounced antiexudative effect of herbal extract and confirmed by a decrease in the number of glycoproteins, sialic acids and middle molecules. Our studies are the basis for clinical trials of licorice dry extract for further recommends its use in clinical practice as an alternative to traditional NSAIDs.
Keywords: licorice extract; antiexudative activity; glycoproteins; sialic acids